The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/laban0506-27
|View full text |Cite
|
Sign up to set email alerts
|

Pain and distress: what really matters?

Abstract: Federal regulations mandate the minimization of both pain and distress in laboratory animals. That no clear definition exists for 'distress' complicates its recognition, quantification, and alleviation. The author argues that IACUCs and investigators should shift their focus from pain to distress, and that in doing so both problems will be better dealt with. She discusses criteria for defining 'significant' distress, and offers suggestions for the conduct of studies to determine levels of distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Distress is often defined as an aversive state in which the animal is unable to adapt completely to stressors and the resulting stress and shows maladaptive behaviour 6,7 . Indeed, pain can be seen as just one possible cause of distress, thus suggesting that quantifying distress of animals might be of greater importance for animal welfare than focusing just on the quantification of pain 8 . However, it has been suggested that distress is not always a consequence of pain 9 ; e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distress is often defined as an aversive state in which the animal is unable to adapt completely to stressors and the resulting stress and shows maladaptive behaviour 6,7 . Indeed, pain can be seen as just one possible cause of distress, thus suggesting that quantifying distress of animals might be of greater importance for animal welfare than focusing just on the quantification of pain 8 . However, it has been suggested that distress is not always a consequence of pain 9 ; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we follow the concept of Koch et al . that one should focus on distress (both pain-related and non-pain-related) when evaluating animal welfare 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For scientific quality, anesthetic techniques need to be reliable and safe, and the effects of the compounds used on the research animals must be well documented. Furthermore, in survival surgical studies, animals should recover quickly and should not to be allowed to suffer pain (Koch, 2006), which is highly significant for both the animal welfare and the quality of the study results. In addition, due to small body size, high body surface area/body weight ratio and high metabolic rate, their mechanisms of thermoregulation and the efficacy of injectable agents can be compromised (Tremoleda et al, 2012); therefore, high doses of these agents are required to induce unconsciousness, producing also detrimental effects on autonomic nervous system.…”
Section: Introductionmentioning
confidence: 99%